Service Quality Strategy with SWOT Analysis to Improve Company Progress - Cahyani, Yuyun Indah (Siber Journal of Transportation and Logistics, 2024)
Service quality strategy with SWOT analysis to increase progress in a company which aims to find out how the influence of using strategy, service quality and SWOT analysis as a way to increase progress in a company. The method used in this research is qualitative, with the method used being a literature study. Strategy is defined as a way to determine the company's main objectives with appropriate actions, which can be used as a guideline for the company's vision and mission. Service quality is closely related to customer experience, which helps them develop a strong relationship with the company's mission. SWOT provides an overview of the weaknesses, strengths, opportunities and threats that each company or activity has in carrying out its operations or business activities. companies need to have a coherent and responsive strategy to overcome challenges and exploit new opportunities. Business strategy is also important in setting a clear direction for the company. The company's goal can be to improve quality to be able to differentiate between the company's positioning and its competitors in terms of what might be of value to customers.